A new balance of power at the 29th World Climate Conference: International climate policies after the US elections - Ole Adolphsen; Jule Könneke (Stiftung Wissenschaft und Politik (SWP), 2024)
The 29th Climate Change Conference (COP29) in Baku revealed a shift in the balance of power in international climate politics following the US elections. While China played a constructive role in the negotiations on international climate finance, vulnerable countries were forced to make painful compromises. Saudi Arabia managed to systematically block progress on mitigation, while middle powers increasingly criticised the EU's climate protection measures. To obviate the risk of isolation and avoid repercussions for its climate and competition agenda, the new European Commission needs to reorientate its climate diplomacy.
Keywords: 320; COP29; World Climate Conference; USA; China; European Union; EU; New Collective Quantified Goal; NCQG; Baku to Belém Roadmap to 1.3T; United Nations Framework Convention on Climate Change; UNFCCC; Carbon Border Adjustment Mechanism; CBAM; Global Gateway; New Collective Quantified Goal (NCQG)